Upward social comparison and social anxiety among Chinese college students: a chain-mediation model of relative deprivation and rumination - 许, 丽娟; 李, 力 (Frontiers in Psychology, 2024)
Background: Social anxiety has consistently emerged as a prominent manifestation of mental health issues among college students. Though the relationship between upward social comparison and social anxiety has been extensively addressed in previous literature, little attention has been paid to the underlying mechanisms at play. Objective: The present study used a questionnaire survey to test whether upward social comparison may be associated with social anxiety in Chinese college students.The mediating role of relative deprivation and rumination was also examined. Methods: In total, 463 college students were recruited to complete four scales, including the Upward Social Comparison Scale, the Relative Deprivation Scale, the Ruminative Thinking Scale, and the Social Anxiety Scale.The results show that upward social comparison was positively correlated with relative deprivation, rumination, and social anxiety (r = 0.30, 0.31, and 0.27; p < 0.01).Second, relative deprivation was positively correlated with rumination and social anxiety (r = 0.40 and 0.17, respectively; p < 0.01). Finally, rumination was positively correlated with social anxiety (r = 0.47, p < 0.01). Moreover, upward social comparison positively predicts social anxiety, with an effect value of 0.12, while rumination plays a mediating role between upward social comparison and social anxiety, with an effect value of 0.07. Separately, the chain mediation of relative deprivation and rumination had an effect value of 0.03. Conclusion: This research highlights the relationship between upward social comparison and social anxiety in Chinese society and revealed the mediating mechanisms between them, deepening our understanding of how upward social comparison increases social anxiety.